Lean process management implementation through enhanced problem solving capabilities - A. Perumal, Puvanasvaran; Megat Ahmad, Megat Mohamad Hamdan; Tang, Sai Hong; Muhamad, Mohd Razali; Hamouda, Abdel Magid Salem (OmniaScience, 2010)
All Original Equipment Manufacturers (OEM) organizations in Aerospace, Automotive and Electronics industries had to upgrade their functions. These organizations including suppliers and solutions providers are duty bound to improve their functions through strategic initiatives. One such initiative is Lean Process Management. Lean Process Management has proven to aid organizations in developing manufacturing and administrative management solutions and make the organization a leaner at the same time a ‘fitter’ one, achieving World Class standards in terms of production, quality, marketing, etc, etc. The issue or problem is, although a number of authors, experts, researchers have discussed the lean process management as part organization centric issues, they failed to provide an effective lean process management system. Besides the need to formulate an effective lean process as suggested by some authors, another important reason suggested is the employee’s development aspect regarding how to unlock the infinite potential of their workforce. This employee’s development is basically the problem solving capabilities of the employees while implementing the Lean through clear cutting protocols or processes of Lean Process Management. The employees need to be developed and equipped to contribute optimally to the process. Because of this scenario, the main objective of this study is to develop an employees development system which the author has acronym or trademark it as People Development System (PDS) to enhance problem solving capability among its employees while implementing the lean process management there. Although, the PDS can be implemented throughout the organization, if it is implemented in a particular department in an organization, it will be feasible to study and analyze its effectiveness in-depth. So, this study documents and analyzes the implementation of Lean process in the Kitting Department of the aerospace company, ABC Company. Qualitative and quantitative measures were also used to document the case study. The outcome of the people development system needs to be measured to understand its value in developing the problem solving capabilities among the employees. Only with developed and equipped employees, the Kitting Department can reduce its wastages, optimize its performance and thereby play a crucial role in making ABC Company a world class organization. As pertinent results of the PDS implementation, in general Kitting Department successfully achieved to meet their Department Key Performance Indicator and particularly the employees’ are also improve by practicing good lean behaviors and skill and knowledge in using lean tools which lead to better leanness level by improving employees’ problem solving capabilities in eliminating waste. On the whole, the lean process management and the resultant PDS is having positive applications, and importantly could also have positive applications in the future as well.